Faktor yang Mempengaruhi Loyalitas Pembaca Majalah Pertanian Trubus Versi Cetak di Tengah Era Media Digital - Ahmad Khairul Nuzuli (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to investigate the factors that influence reader loyalty to Trubus Agriculture Magazine amidst the dominance of online media. Even though print media faces big challenges from online media, its trust and credibility remain high. Using Uses and Gratification Theory as a theoretical framework, this research explores the influence of content quality, ease of access, and reader experience on reader loyalty. With a population of Trubus Agriculture Magazine buyers at the Trubus Yogyakarta Store, a research sample of 50 people was selected using purposive sampling. Simple regression analysis was carried out using SPSS 25. The research results showed a significant relationship between content quality, ease of access, and reader experience and reader loyalty to print media. These findings underscore the importance of these factors in retaining readers in the competitive digital era. The implications of this research provide valuable insights for the print media industry to understand reader preferences and strengthen their marketing strategies. Thus, this research makes an important contribution in understanding the dynamics of mass media in the current digital era.